2022
DOI: 10.3390/jcm11206133
|View full text |Cite
|
Sign up to set email alerts
|

A Case Series of Deep Transcranial Magnetic Stimulation Treatment for Patients with Obsessive-Compulsive Disorder in the Tokyo Metropolitan Area

Abstract: Obsessive-compulsive disorder (OCD) is a chronic illness in which patients do not achieve remission sufficiently with conventional medication. Deep repetitive transcranial magnetic stimulation (dTMS) for OCD neuromodulates the bilateral anterior cingulate cortex (ACC) and dorsal medial prefrontal cortex (mPFC), which are known to be impaired in OCD. While dTMS treatment for OCD has shown effective results overseas, TMS treatment for OCD has rarely been implemented in Japan, and its effectiveness is unknown. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In our recent case series of a different TMS protocol for 26 patients with OCD [ 25 ], we stimulated the medial prefrontal cortex as the therapeutic target with deep TMS using a butterfly coil at high frequency and combined this with an exposure and reaction prevention method before each session of rTMS, and we found that approximately 54% of patients responded to this combined treatment protocol. On the other hand, although the number of patients in this case series was small, the treatment response rate of this study was 67%, even without the combination of the exposure and response prevention method, indicating that the SMA-cTBS therapeutic intervention may be promising as a neuromodulation treatment for OCD, since it has the advantage of a short treatment time within a few minutes, as well as an overall intervention period of 3 to 5 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our recent case series of a different TMS protocol for 26 patients with OCD [ 25 ], we stimulated the medial prefrontal cortex as the therapeutic target with deep TMS using a butterfly coil at high frequency and combined this with an exposure and reaction prevention method before each session of rTMS, and we found that approximately 54% of patients responded to this combined treatment protocol. On the other hand, although the number of patients in this case series was small, the treatment response rate of this study was 67%, even without the combination of the exposure and response prevention method, indicating that the SMA-cTBS therapeutic intervention may be promising as a neuromodulation treatment for OCD, since it has the advantage of a short treatment time within a few minutes, as well as an overall intervention period of 3 to 5 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in this case series, we performed a total of 30 sessions of cTBS treatment targeting bilateral SMA [ 24 ] without any exposure and response prevention and aimed to retrospectively compare the effectiveness of the treatment with the results of our recent case series of OCD treated with TMS combined with exposure and response prevention [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Single-cell immunoglobulin sequencing was performed as described previously ( 24 ). Briefly, plates were removed from -80 °C and centrifuged briefly.…”
Section: Methodsmentioning
confidence: 99%
“…Based on previous studies, the response of patients with OCD to DTMS treatment was determined by whether the total score on the Y-BOCS decreased by 30% or more from baseline[ 32 ]. We summarised the available studies and found that the remission rate of OCD treated with DTMS was 29.22%-53.90%[ 31 , 33 , 34 ].…”
Section: Dtms In Psychiatric Disordersmentioning
confidence: 99%